Modelo de negocio para la creación de un parque infantil ecoturístico en el municipio de Arcabuco, Boyacá (2022)
This project has aim, through the implementation of a research methodology aimed at obtaining statistical data on the latent needs within educational institutions in the field of environmental education, to determine aspects that allow to demonstrate the pedagogical deficiencies around this branch and the importance of providing spaces that allow its approach and eventual solution.